1992
DOI: 10.1111/j.1432-1033.1992.tb17205.x
|View full text |Cite
|
Sign up to set email alerts
|

The primary structure of a protein containing a putative [6Fe‐6S] prismane cluster from Desulfovibrio vulgaris (Hildenborough)

Abstract: The gene encoding a protein containing a putative [6Fe-6S] prismane cluster has been cloned from Desulfovibrio vulgaris (Hildenborough) and sequenced. The gene encodes a polypeptide composed of 553 amino acids (60161 Da). The DNA-derived amino acid sequence was partly confirmed by Nterminal sequencing of the purified protein and of fragments of the protein generated by CNBr cleavage. Furthermore, the C-terminal sequence was verified by digestion with carboxypeptidases A and B. The polypeptide contains nine Cys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

1995
1995
2004
2004

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(18 citation statements)
references
References 58 publications
0
18
0
Order By: Relevance
“…HCP and the gene encoding this protein have previously been isolated from D. vulgaris (Hildenborough) and D. desulfuricans ATCC 27774 [1–4,8,21,22]. Cross‐reactivity with antibodies and hybridization with nucleic acid probes indicated that proteins and DNA sequences with similarity to D. vulgaris HCP and the hcp gene, respectively, also occur in other strictly anaerobic sulfate‐reducing bacteria [2,22]. However, screening of recent sequence databases suggests a much wider distribution of the hcp gene within the bacterial and archaeal kingdoms.…”
Section: Resultsmentioning
confidence: 99%
“…HCP and the gene encoding this protein have previously been isolated from D. vulgaris (Hildenborough) and D. desulfuricans ATCC 27774 [1–4,8,21,22]. Cross‐reactivity with antibodies and hybridization with nucleic acid probes indicated that proteins and DNA sequences with similarity to D. vulgaris HCP and the hcp gene, respectively, also occur in other strictly anaerobic sulfate‐reducing bacteria [2,22]. However, screening of recent sequence databases suggests a much wider distribution of the hcp gene within the bacterial and archaeal kingdoms.…”
Section: Resultsmentioning
confidence: 99%
“…We have found no homology to the E. coli region of fur. However, no consensus promoter sequence has yet emerged from the known D. vulgaris gene sequences (48,51,54). Therefore, based on our present results, the 0.8-kb band could represent either an independent rbr-rdl transcript or a processed (or degraded) version of the fur-rbr-rdl transcript.…”
Section: Resultsmentioning
confidence: 99%
“…2B). The D. vulgaris genome sequence indicated the presence of hcp2 in addition to hcp1, encoding hybrid cluster protein 1, previously referred to as prismane protein (23). Hcps are induced by nitrate, nitrite, nitric oxide, and/or hydrogen peroxide, suggesting a role in nitrogen metabolism and/or oxidative stress defense (2,3,10).…”
Section: Discussionmentioning
confidence: 99%